Phage-displayed peptide targeting on the Puumala hantavirus neutralization site. - Heiskanen, T (1997)
We have selected ligands for Puumala hantavirus, the causative agent of nephropathia epidemica, from a seven-amino-acid peptide library flanked by cysteines and displayed on a filamentous phage. To direct the selection to areas on the virus particle which are essential for infection, phages were competitively eluted with neutralizing monoclonal antibodies specific for the viral glycoproteins. The selected phage populations were specific for the same sites as the antibodies and mimicked their functions. The peptide insert, CHWMFSPWC, when displayed on the phages, completely inhibited Puumala virus infection in cell culture at the same effective concentration as the eluting antibody specific for envelope glycoprotein G2. The binding of the phage clones to the virus and inhibition of infection were not necessarily coincident; Pro-6 was critical for virus inhibition, while consensus residues Trp-2 and Phe-4 were essential for binding. The strategy described can be applied to any virus for production of molecules mimicking the effect of neutralizing antibodies.